Nineteen Eighty-Four : A Novel - Orwell, George (New York Penguin Books, 1986)
In "Nineteen eighty-four", one of the 20th century's great myth-makers George Orwell takes a cold look at the future.
Keywords: Totalitarianism -- England--London -- Political fiction